Attitudes of Pre-clinical Medical Students towards Psychiatric Patients Before and After an Early Clinical Experience - Rudnick, Abraham (Canadian Medical Education Journal, 2011)
Background: Stigma or negative discriminatory attitudes towards psychiatric patients are common in the general public. These attitudes are also demonstrated by medical practitioners and by medical students, which can lead to medical harm to psychiatric patients. This study aimed to improve attitudes of medical students towards psychiatric patients before their clinical rotations. Methods: Second year preclinical medical students participated in a brief structured early clinical experience which involved introduction to a psychiatric patient in a hospital/clinic setting or in a community vocational setting. Students were randomized to either setting. Data were collected one week before, one week after, and 3 months after the early clinical experience by administering the Medical Condition Regard Scale. Results: The students’ attitudes towards psychiatric patients improved, particularly at follow up. Only male student attitudes improved significantly. Conclusion: Further study is required to understand and improve medical students’ attitudes towards psychiatric patients, perhaps particularly in relation to female students’ attitudes.